(untitled) (Research, Society and Development, 2021)
Corn (Zea mays L.) belongs to the Poaceae family, stands out for its great genetic diversity, adapting in different climates. This study aims to study the yield of green and sweet corn grown in Tocantins. The experiments were carried out at the Federal University of Tocantins - UFT, Palmas’s Campus and Federal Institute of Tocantins - IFTO, Paraiso’s Campus, where 4 corn cultivars were planted (C1, C2 and C3 of common green corn and C4 of sweet corn), on different environments, fertilization levels and sowing times. The yield green grains of C4 were similar (p <0.05), by the Scott-Knott test, with C1 and C3 in environments 2 and 4. In environment 1, C1 was similar to C3, and environment 3 to C3 had higher yield of 77%. It is observed that sweet corn grown in Palmas - TO presented a yield green grain of 60%, similar to C1, it is noted that even under different climatic conditions and different corn genotypes, sweet corn showing similar productive viability to green corn. It is concluded that it is important to study the yield of sweet and green corn grains, as they influence productivity.